Pengaruh lama perendaman dan konsentrasi etanol terhadap rendemen pada pembuatan minyak esensial kulit buah jeruk pontianak - Welly Deglas (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
The purpose of this study was to determine how much influence of different immersion duration (1 day, 2 days and 3 days) and ethanol concentration (50%, 70% and 90%) on the yield in the production of essential oils made from Pontianak orange peels. The study was conducted using a Completely Randomized Design (CRD) with factorial pattern: A factor was the level of soaking time (1 day, 2 days, 3 days), and B factor was the ethanol concentration (50%, 70% and 90%) of 3 replications. The highest yield of Pontianak orange peel essential oil was produced in the treatment of immersion for 3 days with ethanol concentration of 90% (A3B3) which was 8.89%. While the lowest yield was obtained in the treatment of 1-day immersion with the ethanol concentration of 50% (A1B1) which was equal to 5.01%. The immersion duration and ethanol concentration affect the colour and pH, whereas the aroma was not significantly affected among samples.